SAT0280 Rapamycin restores the balance between th17 and regulatory t cells in uspa patients. (12th June 2018) - Jinnan, F.; Dan, X.; Chong, G.; Xiaofeng, L.
Abstract : Background: The association of undifferentiated spondyloarthritis (uSpA) with the imbalance of Th17/Treg cells is still unclear. By inhibiting mTOR, rapamycin promotes the proliferation of Treg cells and inhibits the growth of Th17 cells. Objectives: Therefore, we aimed to investigate the status of Treg and Th17 cells in uSpA patients and explore the therapeutic effect of Rapamycin on uSpA patients with imbalanced of Th17 and Treg cells. Methods: Two hundred thirty-seven new onset uSpA patients and 93 healthy controls were enrolled. These patients fulfilled ESSG criteria for SpA but did not fulfill the criteria for any established disease of the group. Both absolute numbers and proportions of Treg (CD4 +CD25+Foxp3+T) and Th17 (CD4 +IL-17+T) cells in peripheral blood were analysed by flow cytometry. The 21 new onset Patients with imbalance of Th17/Treg cells were treated with rapamycin at a dose of 0.5 mg twice for a weeks or every 2 days for 6 weeks combined with conventional treatment (salazosulfapyridine 500 mg three times per day; etoricoxib 60 mg once per day or other NSAIDs drugs). Results: Increase in absolute number and percentage of Th17 (Th17% 1.11±0.66 vs 2.43±1.21, p<0.05; Th17 cells/µl 7.54±4.07 vs 19.54±18.45, p<0.05) and decrease in those of Tregs (Treg% 4.8±1.60 vs 3.35±1.76, p<0.05; Treg cells/µl (33.77±13.67 vs 27.79±28.62, p<0.05) were found in 18.6% (44/237) of patients with uSpA as compared with that of healthy controls. The patients with imbalance of Th17/Treg cells displayed higher BASDAI scores and ESR as compared with other uSpA patients [BASDAI (3.27±1.06 vs 1.13±0.91 P<0.05); ESR (29.27±19.32 vs 21.80±18.34 P<0.05)]. The absolute count of Th17 in 21 patients received rapamycin reduced after 6 weeks (12.35±11.00 vs 6.69±5.54, p<0.05) whereas that of Treg cells showed increase trend but the difference did not reach statistical significance. Conclusions: Absolute number of Treg decreased and that of Th17 cells increased in the peripheral blood of uSpA patients, suggesting that imbalance of the two subsets contributes to the pathogenesis of uSpA. Rapamycin recovered the balance between Th17 and Treg cells in uSpA patients by reducing Th17 cells. References: [1] Cruzat V, et al. Undifferentiated spondyloarthritis: recent clinical and therapeutic advances. J. Curr Rheumatol Rep2010Oct;12(5):311–317. [2] da Cruz Lage R, et al. Undifferentiated spondyloarthritis in a heterogeneous Brazilian population: an eight-year follow-up study. J. Rheumatol Int 2014 Jul;34(7):1019–1023. [3] Heather K, et al. Rapamycin inhibits differentiation of Th17 cells and promotes generation of FoxP3+ T regulatory cells. J. Int Immunopharmacol 2007 Dec;15;7(13):1819–1824. [4] Raychaudhuri SP, et al. IL-23/IL-17 axis in spondyloarthritis-bench to bedside. J. Clin Rheumatol 2016 Jun;35(6):1437–1441. Disclosure of Interest: None declared